Hereditary Emotional Capacities - Redefinition of Emotional Categorizations and Manifestations (American Journal of Human Psychology, 2024)
This paper will attempt to open a marginalized but topical debate on the notion of science and the temporal sustainability of stochastic laws in social sciences. It will offer a new interpretation, through a comparative analogy, aimed at revising the existing pedagogical - psychological - sociological scientific attitudes. The paper tries to define a new line of thought, defined by the limited and essentially unchanged individual capacities of the individual. Our approach is expressed in the view that science is a cognitive-developmental reality, rather than a value system of interpretations and defined lines of thought. What has been done in the area of stochastic regularities, performed categorizations, listed manifestations and the new definitions of “emotions” in the recent decades and what we propose, we will show through a simplified analysis within this paper.